EDUKASI KEPATUHAN PAJAK: MEMBANGUN KESADARAN PAJAK PADA GENERASI Z DAN PRAKTIK PENGISIAN SPT DENGAN APLIKASI E-FILING - Hajar, Hasbullah; Lobi, Abdul Rais; Basri, Anjani; Ulidam, Noho (Al-Mulk: Jurnal Pengabdian Masyarakat, 2024)
The purpose of community service (PMM) is to provide tax education to the Z generation in Ternate City about the importance of taxes for the nation and state. This PKM also provides training about how to fill out and report SPT via the e-filing application. This PKM is provided by a collaborative PKM team consisting of lecturers and students from the sharia accounting study program. The PKM method is Participatory Action Research (PAR). Based on the pre-test carried out, it was discovered that from 42 participants, only 40% of them had a good basic understanding of the importance of taxes and none of the participants knew how to use the e-filing application. And after PKM  inished, total number of participants who understood the total  importance of taxes and how to use the e-filing application increased to 96%.Keywords: Education; Tax; E-filing;  Z Generation.